Kebijakan Dikotomi Pendidikan di Indonesia pada Masa Reformasi - Muh Subhan Ashari (AN NUR: Jurnal Studi Islam, 2015)
Dichotomy is the division of two parts, splitting the two parts, or forked section. Some people difine dichotomy as the divisions of two parts which againt each other. Dichotomy of education means separation between religion subjects and science subjects, both formal and informal. Bipolar-dichotomous mindset has brought uncomfortable consequences for the life and welfare of mankind. Because it will make man alienated from the values of spirituality and morality, alienated from himself, his family and the surrounding community. This paper aims to find the traces of policy of dichotomy in Indonesian education, especially in a period of reform, and to find the root of policy dichotomy in Indonesian education. In addition, this paper also aims to explains the Islam views of the problems of dichotomy in education